2020
DOI: 10.1111/odi.13256
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non‐surgical periodontal therapy on glycemic control in diabetic patients: A randomized controlled trial

Abstract: Aim The present study aimed to monitor the clinical outcomes and the metabolic response of periodontal therapy (non‐surgical) in patients with periodontitis (chronic) and uncontrolled diabetes (type 2). Methods Eighty‐eight subjects with periodontitis (chronic) and uncontrolled diabetes (type 2) were enrolled in this controlled trial and allocated randomly to the test group (44 patients were received immediate periodontal therapy) or the control group (44 patients were received delayed periodontal therapy). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
(49 reference statements)
0
15
0
2
Order By: Relevance
“…No significant heterogeneity was detected (p = 0.162; I 2 = 45.1%). Influence analysis showed that deleting Makaky et al's study [25] increased the width of the 95% confidence interval, but the WMD did not change significantly and was still significant (WMD -0.983, 95% CI -1.904, -0.061; p = 0.037), indicating that the pooled result was relative stable (ESM Fig. 2b).…”
Section: Baseline Hba1c Level Between 8 and 9%mentioning
confidence: 94%
“…No significant heterogeneity was detected (p = 0.162; I 2 = 45.1%). Influence analysis showed that deleting Makaky et al's study [25] increased the width of the 95% confidence interval, but the WMD did not change significantly and was still significant (WMD -0.983, 95% CI -1.904, -0.061; p = 0.037), indicating that the pooled result was relative stable (ESM Fig. 2b).…”
Section: Baseline Hba1c Level Between 8 and 9%mentioning
confidence: 94%
“…La mayoría de estudios que evaluaron el impacto del tratamiento periodontal en los valores de hemoglobina glicosilada evidenciaron una reducción significativa de este marcador glucémico (El-Makaky & Shalaby, 2020;Rapone et al, 2021;Bala & Kumari, 2021;Qureshi et al, 2021) esto es clínicamente relevante, pues una disminución en el nivel de hemoglobina glicosilada, por más limitada que sea, tiene un impacto favorable en la reducción del riesgo de complicaciones en pacientes diabéticos (Chen et al, 2021) tal como se evidenció en un estudio de seguimiento de 10 años, sobre el control de la glucosa en pacientes con DM, en el que, una disminución de la hemoglobina glicosilada de 1 % se tradujo en la reducción del 35 % de riesgo de microangiopatía diabética, e incluso una disminución de 0,2 % de la media de hemoglobina glicosilada significó la reducción del 10 % de la mortalidad en estos pacientes (Holman et al, 2008). En una reciente revisión sistemática de ensayos clínicos aleatorizados (Benrachadi et al, 2019) los autores reportaron que la terapia periodontal contribuyó al control de la hemoglobina glicosilada en pacientes diabéticos con periodontitis.…”
Section: Discussionunclassified
“…The elevated serum level of IL-1β, IL-6 and TNF-α that, associated with periodontitis, antagonize the action of insulin and increase the insulin resistance; re-establishing good periodontal health in type 2 diabetics with periodontal disease has the potential of greatly improving metabolic control and systemic inflammatory challenge, and therefore non-surgical periodontal therapy can significantly reduce the level of HbA1c in T2DM patients with periodontitis [21,29].…”
Section: Relationship Between Periodontitis and Diabetesmentioning
confidence: 99%